2006
DOI: 10.1002/jcp.20944
|View full text |Cite
|
Sign up to set email alerts
|

Low‐intensity pulsed ultrasound (LIPUS) induces RANKL, MCP‐1, and MIP‐1β expression in osteoblasts through the angiotensin II type 1 receptor

Abstract: Constant mechanical stress is essential for the maintenance of bone mass and strength, which is achieved through the cooperative functions of osteoblasts and osteoclasts. However, it has not been fully elucidated how these cell types mediate mechanical signals. Low-intensity pulsed ultrasound (LIPUS) therapy is a recently developed method for application of mechanical stress, and is used clinically to promote bone fracture healing. In the present study, we applied LIPUS to osteoblasts at different stages of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
78
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 35 publications
5
78
0
Order By: Relevance
“…AT1 receptor antagonists also interfere with lipopolysaccharide activation of RAW264.7 osteoclast-like cells (26). Second, ultrasound (mechanical strain) has been shown to increase RANKL, MCP-1, and MIP in osteoblasts by signaling via the AT1 receptor (21). Third, high blood pressure has been associated with bone loss in various clinical studies in humans (14,30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AT1 receptor antagonists also interfere with lipopolysaccharide activation of RAW264.7 osteoclast-like cells (26). Second, ultrasound (mechanical strain) has been shown to increase RANKL, MCP-1, and MIP in osteoblasts by signaling via the AT1 receptor (21). Third, high blood pressure has been associated with bone loss in various clinical studies in humans (14,30).…”
Section: Discussionmentioning
confidence: 99%
“…In bone tissue, Ang II was reported to promote bone resorption via the AT1 receptor in cell culture system and in ovariectomized mice and rats (19). Expression of AT1 receptor was observed in cultured osteoblasts (21), and Ang II inhibit differentiation and bone formation via the AT1 receptor in rat calvarial osteoblastic cells (22). In contrast to the AT1 receptor, no significant effect was observed in cells by the AT2 receptor blocker in rat calvarial cell (22) or in the co-cultures of human osteoblast and osteoclast precursor cells (19).…”
mentioning
confidence: 99%
“…It has been reported that MAPK family proteins, including ERK, p38 MAPK, and c-Jun N-terminal kinase (JNK), are activated by various mechanical stimuli (14). We and other groups have reported previously that ERKs are crucial signaling molecules in LIPUS-induced cellular responses (11,15). However, detailed signaling pathways of MAPK activation by mechanical stress are still poorly understood.…”
Section: Multipotent Mesenchymal Stem Cells (Mscs)mentioning
confidence: 99%
“…Several in vitro studies have shown that LIPUS facilitates osteoblast differentiation, represented by increased Osteocalcin mRNA expression and extracellular calcification (10). We have reported previously that mRNA expression of several chemokines in mature osteoblasts that is mediated by angiotensin 2 type 1 receptor is also induced with LIPUS treatment (11). In the site of bone fracture, MSCs are the cellular source of osteoprogenitor cells (12).…”
Section: Multipotent Mesenchymal Stem Cells (Mscs)mentioning
confidence: 99%
“…However, this study shows that mechanical stress up-regulates RANKL mRNA expression despite the interception of VEGF/VEGFR-1. It was reported that angiotensin II type 1 receptor (AT1), a known mechanoreceptor in cardiomyocytes, up-regulates RANKL mRNA expression to some extent in mechanically stressed osteoblasts (34). Such receptors of mechanical stimulation are also expected to control RANKL mRNA expression.…”
Section: Discussionmentioning
confidence: 99%